INSTITUTIONAL CAPACITY DEVELOPMENT OF TOURISM VILLAGE IN SUKABUMI DISTRICT - Julaeha, Siti; Rahmawati, Rita; Harini, Sri (Administratie: Jurnal Administrasi Publik, 2021)
This research is motivated by the potential for the development of tourist villages in Sukabumi Regency, which has not been fully maximized due to the limited role of social and cultural aspects within the community, as well as the institutional government model for managing the existing tourist destinations in Sukabumi Regency. This study aims to identify the institutional factors that either support or hinder the development of tourist villages in Sukabumi Regency. Employing a descriptive method and a qualitative approach, this research utilizes literature studies related to tourist villages, local wisdom, tourism development, and institutional capacity strengthening. The findings reveal that there are institutional factors that support the development of tourist villages. Several influencing factors include information technology, human resources, and collaboration among various stakeholders in tourism development. The recommendations from this study underscore the need to bolster the institutional capacity of tourist villages by enhancing structures with a focus on Information Technology, expanding and training human resources to cultivate skilled and innovative individuals, and progressively and intensively fostering collaborations with diverse entities, including Entrepreneurs, Academics, Media, Civil Society Organizations/Communities, and the general public.